How to define and measure informal employment in developed countries? A case of Poland - Dagmara Nikulin (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
The main aim of this article is to point out the possible measures of how to improve the study of informal employment in developed countries. We choose the case of Poland to examine whether the existing definitions and measurement methods are suitable for indicating the prevalence of informal employment. Firstly, we present the most popular definitions of informal employment, secondly we show the existing research on informal employment in Poland, and thirdly we assess the previous estimations of informal employment in Poland with regard to the definition's scope. Finally, we propose some improvements that would help in studying this phenomenon in Poland. Through a critical analysis of existing research on informal employment we contribute to the existing literature in two ways: (i) by constructing the definitional frames of informal employment in Poland; and (ii) by pointing out the possible extensions of surveys devoted to informal employment in developed countries.
Keywords: E26; J46; O17; 330; informal employment; Poland; undeclared work; shadow economy